Deep brain stimulation for neurodegenerative diseases - Shashkinl, Ch.; Akshulakovl, S.; Makhambetovl, Y.; Shpekovl, A.; Dzhamantaeval, B.; Akhmetzhanovl, V. (My University, 2016)
Neurodegenerative diseases (ND) with movement and cognitive disorders are very complicated diseases to treat. Sometimes medical treatment is not successful or results in unpleasant complications. Nowadays neurosurgical treatment as deep brain stimulation (DBS) became possible in clinical medicine. http://nur.nu.edu.kz/handle/123456789/1514
Keywords: Neurodegenerative diseases